The impact of digitization on the Algerian university’s openness to its socio-economic environment _The Innovative Projects Monitoring System platform as a model - KERROUMI , Yehya; GODMANE , Mohammed (Journal of Science and Knowledge Horizons, 2025)
This study aims to examine the realities and challenges of the digital transformation adopted by the Ministry of Higher Education and Scientific Research across its various university institutions by focusing on the contribution of the Innovative Projects Monitoring System platform in promoting an entrepreneurial culture among students. It also aims to assess the responsiveness of the Algerian society in general, and students in particular, to this new culture. The study concluded with a set of findings, foremost of which is that the Innovative Projects Monitoring System platform has contributed to spreading the entrepreneurial culture among university students. Additionally, the platform undertakes several tasks aimed at enhancing the students’ knowledge level in the field of entrepreneurship.